Advantages and Design of PROMIS Questionnaires. Issue 10 (December 2020) - Gibbons, Denys; Welch-Phillips, Adanna; Ahern, Daniel P.; Butler, Joseph S.
Abstract : The Patient-Reported Outcomes Measurement Information System (PROMIS) is a National Institute of Health initiative to improve the measurement of clinically important symptoms and outcomes. Patient-Reported Outcomes capture health outcomes that are relevant to the daily functioning of the patient and include the monitoring of physical, mental, and social health. PROMIS offers a standardized tool to measure Patient-Reported Outcomes for use in both the clinical and research setting. It is a flexible and dynamic tool for both patient and clinician, and its use is continuing to grow internationally. This article discusses the rationale and design of this tool, as well as its advantages to both research and clinical practice.